Hubungan Keeper dan Harimau Sumatera di Taman Marga Satwa Budaya Kinantan, Bukittinggi, Sumatera Barat - Basyarul Aziz; Khoirun Nisa Aulia Sukmani (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
This paper discusses multispecies anthropology, which refers to an approach involving various forms of life, recognizing that humans are not the only significant subjects in ecosystems. It is an anthropological approach that expands the focus of study to include the relationships between humans and other species, including animals, plants, microorganisms, and non-human entities. The paper explores the relationship between humans and Sumatran tigers at the Kinantan Wildlife and Cultural Park in Bukittinggi.The Sumatran tiger is critically endangered due to habitat loss, ecosystem degradation, and most importantly, the high-intensity human-tiger conflict. This has created conditions where tigers are relocated to enclosures or zoos. Tigers in zoos are often explored for economic or research purposes, creating a new agency for tigers as both